2014
DOI: 10.1371/journal.pone.0101066
|View full text |Cite
|
Sign up to set email alerts
|

Common Mental Disorders in Public Transportation Drivers in Lima, Peru

Abstract: BackgroundTraffic related injuries are leading contributors to burden of disease worldwide. In developing countries a high proportion of them can be attributed to public transportation vehicles. Several mental disorders including alcohol and drug abuse, psychotic disorders, mental stress, productivity pressure, and low monetary income were found predictors of high rates of traffic related injuries in public transportation drivers. The goal of this study was to estimate the prevalence of common mental disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
(16 reference statements)
3
5
1
2
Order By: Relevance
“…The information in this study showed that more than 40% of drivers had experienced symptoms of anxiety and sleeplessness. These symptoms were reported in 23.6% and 14.5% of drivers of Peru (16) and the United States (1). Since driving requires continuous analysis of acquired data from the vehicle's condition and surroundings as well as a prediction of behaviors of other drivers, anxiety would be a destructive factor leading to accidents (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The information in this study showed that more than 40% of drivers had experienced symptoms of anxiety and sleeplessness. These symptoms were reported in 23.6% and 14.5% of drivers of Peru (16) and the United States (1). Since driving requires continuous analysis of acquired data from the vehicle's condition and surroundings as well as a prediction of behaviors of other drivers, anxiety would be a destructive factor leading to accidents (7).…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no comprehensive information about depression among drivers, some studies have focused on this issue. Depression has been reported among 26.9% of truck drivers in the United States (12), 33% of taxi drivers in Nigeria (1), and 15.6% of drivers in Peru (16). Depression affects the drivers' ability to focus (6) and was introduced as one of the psychological consequences of driving (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os estudos selecionados foram realizados no Brasil (N=12) (9,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) , no Peru (N=2) (26)(27) , na Índia (N=2) (28)(29) , na Turquia (N=1) (30) , em Taiwan (N=1) (31) , na Tailândia (N=1) (32) , na Coreia do Sul (N=1) (33) e na Sérvia (N=1) (34) . Dentre os 21 estudos selecionados, dois foram teses de doutorado (15)(16) e duas dissertações de mestrado (9,17) .…”
Section: Introductionunclassified
“…It has been suggested that some personality traits may be potential predictors of hazardous driving behaviors [16]. Ruiz-Grosso et al [17] have shown that common mental disorders such as alcohol abuse, major depressive episode, anxiety symptoms, and burnout syndrome are higher in public transportation drivers than in the general population [17].…”
Section: Introductionmentioning
confidence: 99%